Intra Specific Relationships and Biochemical Composition of Laportea Aestuans (L.) Chew, Sida Rhombifolia L. And Commelina Verginica L. in Lagos State - E. Ani; Ofodile, L. N.; Nwakanma, N. M. C.; A. Saanu; Ayodeji, A. A.; Emeronye, I. G.; Balogun, R. I.; Ikutegbe, G. (Iraqi Journal of Science, 2023)
Laportea aestuans L. (Chew), Commelina virginica (L.) and Sida rhombifolia (L.) are common wild plants used in treating several ailments including diarrhea, dysentery, hernia, oedema, ulcers and many more in traditional African medicine especially, Nigeria. The potentials of Random Amplified polymorphic DNA (RAPD) primers in delimiting intra-specific variation in L. aestuans, C. virginica and S. rhombifolia was assessed using three RAPD primers. Plant and soil samples were collected from 19 local government areas in Lagos State and assessed for genetic and biochemical relationships. A total of 56 bands were produced of which 44 were polymorphic. Maximum number of bands (21) was produced by OPY20 while OPC04 produced minimum number of bands (14). The maximum and minimum percentage polymorphisms were 100% (OPC04) and 50% (OPA12), The dendrogram of genetic diversity had a genetic distance range of 0.57 to 1.00, 0.58 to 1.00 and 0.52 to 1.00 and clustered at 0.57, 0.58, 0.52 implying 57%, 58%, 52% similarity and 43%, 42% and 48% variability for L. aestuans, C. virginica and S. rhombifolia respectively. Results of phytochemical analysis show that S. rhombifolia is particularly high in steroids (I134.19±0.23), flavonoids (118.65±0.18), phenolics (125.25±1.43), alkaloids (63.56±0.11) and triterpenes (72.44±0.12) but low in saponins (23.29±0.05), glycosides (6.79±0.01) and tannins (7.10±0.02).